Public perception towards refugees and migrants / Amira Nurain Ahmad Anuar and Nur Fatihah Chak - Ahmad Anuar, Amira Nurain; Chak, Nur Fatihah
Refugees and migrants are known as a group or individuals that are vulnerable and have been compelled from their state or home nations due to the issue of nationality, employment, lack of access rights and other circumstances. In other words, the refugees and migrants fled because of problems such as statelessness, violence, war and poverty. Due to this issue, refugees and migrants that want to keep survive and gain a better life choose to fled by find other state that having a strategic location, yearning shelter from the chaos of their home nation, and find a state that have a good economy potential; therefore, Malaysia be a popular destination for refugees and migrants. Thus, a huge number of admissions could create a perception toward the public. Due to this issue, a survey was conducted to assess the public perception towards refugees and migrants in Malaysia. This study included around 302 respondents from general people who filled out questionnaires. The research conducted in purpose to investigate the level of concern among public people, examine the admission of refugees and migrants in terms of economy, social and security and identify what is the main factor that can influence public people's perception toward refugees and migrants.